Architectural acoustics illustrated - Ermann, Michael (Michael A.) (Hoboken, New Jersey Wiley, 2015)
"Translates the quantitative and qualitative content of acoustics into the graphic language of architecture and outlines the best practices for limiting or mitigating noise in buildings"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Architectural acoustics; Architectural acoustics -- Pictorial works